Sexual Development of the Hermaphroditic Scallop Argopecten irradians Revealed by Morphological, Endocrine and Molecular Analysis - Wei, Huilan; Li, Wanru; Liu, Tian; Li, Yajuan; Liu, Liangjie; Shu, Ya; Zhang, Lijing; Wang, Shi; Xing, Qiang; Zhang, Lingling; Bao, Zhenmin (Frontiers in Cell and Developmental Biology, 2021)
Simultaneous or functional hermaphrodites possessing both ovary and testis at the same time are good materials for studying sexual development. However, previous research on sex determination and differentiation was mainly conducted in gonochoristic species and related study on the simultaneous hermaphrodites is still limited. In this study, we conducted a combined morphological, endocrine and molecular study on the gonadal development of a hermaphroditic scallop Argopecten irradians aged 2- to 10-month old. Morphological analysis showed that sex differentiation occurred at 6 months of age. By examining the dynamic changes of progesterone, testosterone and estradiol, we found testosterone and estradiol were significantly different between the ovaries and testes almost throughout the whole process, suggesting the two hormones may be involved in scallop sex differentiation. In addition, we identified two critical sex-related genes FoxL2 and Dmrt1L, and investigated their spatiotemporal expression patterns. Results showed that FoxL2 and Dmrt1L were female- and male-biased, respectively, and mainly localized in the germ cells and follicular cells, indicating their feasibility as molecular markers for early identification of sex. Further analysis on the changes of FoxL2 and Dmrt1L expression in juveniles showed that significant sexual dimorphic expression of FoxL2 occurred at 2 months of age, earlier than that of Dmrt1L. Moreover, FoxL2 expression was significantly correlated with estradiol/testosterone ratio (E2/T). All these results indicated that molecular sex differentiation occurs earlier than morphological sex differentiation, and FoxL2 may be a key driver that functions through regulating sex steroid hormones in the scallop. This study will deepen our understanding of the molecular mechanism underlying sex differentiation and development in mollusks.